2018
DOI: 10.1002/cam4.1574
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in hepatocellular carcinoma: Functions and implications

Abstract: At present, as hotspot members of the noncoding RNA network, circular RNAs (circRNAs) with distinct properties and diverse pathophysiological functions are being increasingly delineated. CircRNAs play roles at the epigenetic, transcriptional and posttranscriptional regulatory levels. Major studies have focused on their functions as efficient microRNA sponges. The validated number of endogenous circRNAs involved in hepatocellular carcinoma (HCC) continues to increase. Altered circRNA expression is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 78 publications
(171 reference statements)
3
91
0
Order By: Relevance
“…CircRNAs may function as ceRNAs to retain endogenous RNA and regulate the expression of related genes . For example, circLARP4 from the LARP4 pre‐mRNA inhibits the occurrence and progression of GC by affecting the expression of cavernous miR‐424 and increasing the expression of LATS1 …”
Section: Biological Functions Of Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs may function as ceRNAs to retain endogenous RNA and regulate the expression of related genes . For example, circLARP4 from the LARP4 pre‐mRNA inhibits the occurrence and progression of GC by affecting the expression of cavernous miR‐424 and increasing the expression of LATS1 …”
Section: Biological Functions Of Circrnasmentioning
confidence: 99%
“…(ii) Specificity: circRNAs are expressed in a tissue‐specific and developmental stage‐specific way. In particular, many studies have shown that circRNAs are distinctively expressed between cancerous and noncancerous tissues . (iii) Universality: circRNAs are considered to be the most widely distributed molecules in human cells.…”
Section: Tumor‐suppressive Circrnas May Be Used As Tumor Biomarkersmentioning
confidence: 99%
“…Then, we demonstrated that circARNT2 was upregulated in HCC tissues and associated with cisplatin resistance in HCC. To further validate whether circARNT2 functionally required for cisplatin resistance, we performed loss-of-function studies by CircRNAs may act as transcription regulators or as sponges for small RNA regulators, which compete for microRNA (miRNA) activity in the process of regulating cell proliferation 22 . Most circRNAs have miRNAbinding sites that can be used as miRNA sponges to inhibit the regulation of miRNAs on downstream target genes by a large number of miRNAs in cancers 23 .…”
Section: Discussionmentioning
confidence: 99%
“…137 Overall, circRNAs played key roles in tumorigenesis and development, epigenetic regulation, drug resistance, and could be considered as immune-associated biomarker and therapeutic target in HCC. [138][139][140][141][142][143][144] Regardless, more in-depth study of circRNA biofunctions in HCC is greatly desired.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%